Can social behaviour drive accessory olfactory bulb asymmetries? Sister species of caviomorph rodents as a case in point - Fernández‐Aburto, Pedro (J Anat, 2019)
In mammals, the accessory olfactory or vomeronasal system exhibits a wide variety of anatomical arrangements. In caviomorph rodents, the accessory olfactory bulb (AOB) exhibits a dichotomic conformation, in which two subdomains, the anterior (aAOB) and the posterior (pAOB), can be readily distinguished. Interestingly, different species of this group exhibit bias of different sign between the AOB subdomains (aAOB larger than pAOB or vice versa). Such species‐specific biases have been related with contrasting differences in the habitat of the different species (e.g. arid vs. humid environments). Aiming to deepen these observations, we performed a morphometric comparison of the AOB subdomains between two sister species of octodontid rodents, Octodon lunatus and Octodon degus. These species are interesting for comparative purposes, as they inhabit similar landscapes but exhibit contrasting social habits. Previous reports have shown that O. degus, a highly social species, exhibits a greatly asymmetric AOB, in which the aAOB has twice the size of the pAOB and features more and larger glomeruli in its glomerular layer (GL). We found that the same as in O. degus, the far less social O. lunatus also exhibits a bias, albeit less pronounced, to a larger aAOB. In both species, this bias was also evident for the mitral/tufted cells number. But unlike in O. degus, in O. lunatus this bias was not present at the GL. In comparison with O. degus, in O. lunatus the aAOB GL was significantly reduced in volume, while the pAOB GL displayed a similar volume. We conclude that these sister species exhibit a very sharp difference in the anatomical conformation of the AOB, namely, the relative size of the GL of the aAOB subdomain, which is larger in O. degus than in O. lunatus. We discuss these results in the context of the differences in the lifestyle of these species, highlighting the differences in social behaviour as a possible factor driving to distinct AOB morphometries.